Millimeter Wave Radar Hardware and Signal Processing - Waldschmidt, Christian; Bonfert, Christina; Grebner, Timo.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book covers millimeter-wave radar technology as used today in advanced applications such as automated driving and industrial sensor technology. Each topic is discussed from a comprehensive systems perspective, thoroughly addressing both signal processing and hardware aspects, along with their interconnections. After a solid introduction to the basics and applications of radar sensors, the focus shifts to the fundamental operating principles of these sensors. Separate chapters then cover signal processing and hardware concepts in detail. Finally, the book concludes with an in-depth discussion of specialized radar techniques, including imaging radar.
Fundamentals -- Radar types, modulation methods, and radar imaging -- Radar hardware -- Radar techniques.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Telecommunication; Control engineering; Robotics; Automation; Optics; Signal processing; Microwaves, RF Engineering and Optical Communications; Control, Robotics, Automation; Optics and Photonics; Signal, Speech and Image Processing